The relative health related quality of life of veterans with Parkinson's disease. Issue 2 (1st February 2003) - Gage, H; Hendricks, A; Zhang, S; Kazis, L
Abstract : Objectives: To use databases of the US Veterans Health Administration (VHA) to describe the impact of Parkinson's disease on health related quality of life (HRQoL) of veterans; to compare the HRQoL of veterans with Parkinson's disease with that of veterans reporting eight other neurological or chronic conditions; and to estimate the unique effect of Parkinson's disease on HRQoL. Methods: Respondents to the VHA 1999 large national health survey of veteran enrollees with a diagnosis of Parkinson's disease in VHA treatment files for the fiscal years 1997–1999 were identified by merging databases. The survey incorporated the Veterans SF-36, a well validated generic measure of HRQoL and functional status. This was used to compare patient groups. Mean physical (PCS) and mental (MCS) component summary scores were calculated for Parkinson's disease and eight other diseases by multivariable regressions that adjusted for age, sex, race, education, and 15 mental and physical co-morbid conditions that were self reported in the survey. Results: Of 887 775 survey respondents, 14 530 (1.64%) had a Parkinson's disease diagnosis. Controlling for sociodemographic factors and co-morbidities, veterans with Parkinson's disease had PCS and MCS below veterans with angina/coronary heart disease, arthritis, chronic low back pain, congestive heart failure, diabetes, and stroke. Veterans with spinal cord injury reported slightly lower PCS than veterans with Parkinson's disease (32.38 v 32.72; 0.03 of 1 SD). Veterans with depression reported markedly lower MCS than veterans with Parkinson's disease (35.94 v 41.48; 0.55 of 1 SD). The unique effect of having Parkinson's disease on HRQoL was to lower PCS and MCS by 4.10 and 3.42 points (0.41 and 0.34 of 1 SD), respectively. Conclusions: The analysis quantifies the negative impact of Parkinson's disease on HRQoL, after controlling for sociodemographic factors and co-morbidities. Compared with eight other chronic conditions, Parkinson's disease imposes a relatively heavy burden on US veterans in the VHA health care system.